Influence of crumb rubber modifier on performance characteristics of stone mastic asphalt /Asim Hassan Ali - Asim Hassan, Ali (2013)
In asphalt concrete (AC), bitumen as a binder serves two major functions in road pavement; first, to hold the aggregates firmly and secondly, to act as a sealant against water. However, due to several distresses like fatigue failure, the performance and durability of certain characteristics in bitumen are highly affected by changes with time which can lead to the cracking of pavements. To prevent pavement distresses there are various solutions such as adopting new mix designs or utilisation of asphalt additives. Using asphalt additives in highway construction is known to provide virgin bitumen better engineering properties. Scrap tyres lead to grave disposal problems. However, with the use of scrap tyres in asphalt pavements in the form of an additive, they are advantageous in minimising environmental pollution and maximising natural resource conservation. The primary aim of this study was to investigate the effect of adding crumb tyre rubber as a modifier to Stone Mastic Asphalt (SMA) mixture performance properties. This study investigated the essential aspects of modified asphalt binder and mixtures in order to better understand the influence of CRM modifiers on the physical-rheological properties of asphalt binder and fatigue resistance of SMA mixture. In this study, 80/100 penetration grade bitumen was used; modified with crumb rubber (CRM) at five different modification levels namely 6 , 12, 16 and 20% respectively by weight of the bitumen. The physical properties of modified bitumen samples were performed using the classic binder tests namely, penetration test, softening point test, ductility test and elastic recovery test. The rheological properties for asphalt binder were conducted using Superpave tests of Brookfield viscosity and dynamic shear rheometer (DSR). The stiffness and mechanical properties as well as fatigue characteristics of (SMA) mixtures produced with and without the crumb rubber were investigated using IDT and ITFT on varying binder content.The results of the study concluded that rubber crumb content plays a main role in influencing the performance and rheological properties of rubberised bitumen binders. The increase in rubber crumb content was from 6 - 20% thus indicating a linear increase in softening point, viscosity, elastic recovery and complex shear modulus. The resilient modulus (Mr) of modified SMA samples including different percentages of CRM was obviously higher in comparison with that of unmodified samples. In addition, crumb rubber content significantly enhanced durability of crumb rubber modified bitumen and led to better aging resistance. Thus, the crumb rubber modified bitumen was less susceptible to temperature susceptibility. With the presence of crumb rubber, the fatigue life of crumb rubber modified bitumen significantly improved. The resistance of crumb rubber in producing horizontal tensile stresses attenuated the production of vertical cracks and deterred these cracks from diffusing along the diameters of the asphalt samples. This in turn improved the fatigue life of reinforced samples. Besides aspiring to decrease piling up of waste materials in the environment, utilising waste tyre rubber has improved the characteristics of engineering structure and materials in asphalt production and comparable industries. Consequently, it has also reduced construction rehabilitation and maintenance costs.